Does total biopsy core length in prostate fusion biopsy affect the diagnosis of clinically significant prostate cancer? (Annals of Medical Research, 2024)
Aim: The aim of our study was to determine the optimal total core length for multiparametric magnetic resonance imaging (MpMRI)-guided prostate fusion biopsy (PFB) that would standardize clinical practice and maximize the detection rate of clinically significant prostate cancer (csPC) while reducing procedural complications, overdiagnosis, and cost.Materials and Methods: A total of 212 patients with at least 1 lesion with Prostate Imaging Reporting and Data System score of  ≥3 were evaluated retrospectively. Biopsy core lengths from the lesions were summed, and total core lengths (TCL) were calculated. Multiple logistic regression analyses were conducted for PIRADS 3, 4, and 5 lesions and the effects of TCL on the detection of csPC were analyzed separately.Results: A total of 365 lesions were detected by MPMRI in 212 men included in the study. The mean TCL was 43.66 ± 12.91 mm in PIRADS 3 lesions, 47.71 ± 11.78 mm in PIRADS 4 lesions, and 60.36 ± 14.64 mm in PIRADS 5 lesions. As TCL increased, the probability of detecting both csPC (1.26-fold per unit increase in TCL) and clinically insignificant prostate cancer (cIPC)(1.25-fold per unit increase in TCL) increased for PIRADS 3 lesions at a statistically significant level,while for PIRADS 4 lesions, only the probability of detecting csPC (1.13-fold for each unit increase in TCL) increased.Conclusion: This study has shown that the frequency of PCa detection rises with increasing TCL. For PI-RADS 3, both csPC and cIPC rise with increasing TCL, whereas for PI-RADS 4 only the frequency of csPC rises.
Keywords: Clinically significant prostate cancer; Multiparametric magnetic resonance imaging; Prostate fusion biopsy; Total core length